Well Log Analysis and Interpretation for Khasib,Tanuma, and Sa’di formations for Halfaya Oil Field in Missan Govenorate-Southern Iraq - Al-maini, Arjwan Hamid; Nasser, Mad’hat E. (Iraqi Journal of Science, 2018)
The study intends to interpretation of well logs to determine the petrophysical parameters for Khasib, Tanuma, and Sa’di formations in Halfaya Oil Field. Where this field is located 30 kilometers south-east of the Amara city and it is considered as one of the important fields in Iraq because of the high production of oil, because Khasib, Tanuma, and Sa’di are f carbonates reservoirs formations and important after the Mishrif Formation because of the lack of thickness of the formations compared to the amount of oil production. The Matrix Identification (MID) and the M-N crossplot were used to determine the lithology and mineralogy of the formations; through the diagrm it was found the three formations consisted mainly of calcite with some dolomite. Density – Neutron cross plot for lithology identification which shows that the formations are mainly consist of limestone with little shale